PERSEPSI MASYARAKAT TERHADAP KUALITAS BUS TRANS MEBIDANG - Yusuf Aulia Lubis; Janer Napitupulu (JURNAL ILMIAH TEKNIK SIPIL, 2021)
Transportation is a very vital thing that supports daily human life and the movement of logistics goods. The transportation system is said to be good if the cost is economical and affordable. However, it seems that the city of Medan has not been implemented; only the costs are determined by the government and public transport organizations without involving the community. The low quality of service in terms of security, comfort, feasibility, convenience and efficiency of public transportation, gives a feeling of being less comfortable and safe for users of public transportation services. The increasing number of people who use private vehicles in the city of Medan is increasing traffic congestion which results in longer travel times, because there are many vehicles and lower speeds. Therefore, private vehicle users cause congestion, inefficiency in the use of road space, and reduce road capacity. To reduce congestion in the city of Medan, the Medan city government entered into cooperation with Deli Serdang Regency and Binjai City; Trans Me Field Bus was established to overcome traffic jams. Therefore, researchers are interested in knowing the service quality of buses through public perception